A tribo-positive Fe@MoS2 piezocatalyst for the durable degradation of tetracycline: degradation mechanism and toxicity assessment. Issue 6 (18th May 2020) - Meng, Fanqing; Ma, Wei; Wang, Yinglong; Zhu, Zhaoyou; Chen, Zhen; Lu, Guang
Abstract : Durable elimination of tetracycline and its toxicity by a tribo-positive Fe@MoS2 piezocatalyst via ball-milling activation. Abstract : The elimination of antibiotics by piezo-catalysis has recently attracted considerable attention due to its advantages in engineering applications. However, the risk assessment of target antibiotics and their degradation intermediates during the piezo-degradation process are rarely researched. Herein, a tribo-positive Fe@MoS2 piezo-catalyst with a significantly extended lifetime was synthesized via a simple mechanochemical process. The as-prepared Fe@MoS2 showed superior piezo-catalytic activity via ball-milling activation. The characterization and density functional theory calculation results demonstrated that the high piezoelectric property of Fe@MoS2 is ascribed to its few-layered microstructure and semi-metallic nature. The destruction of its piezo-catalytic sites was successfully eliminated by using the wet ball-milling method as the driving force. After 50 cyclic tests, the piezo-degradation efficiency of Fe@MoS2 for tetracycline still remained above 99%. The radical quenching results and electron paramagnetic resonance spectra indicated that both ˙OH and 1 O2 were generated and took part in the degradation of tetracycline. A possible degradation pathway was proposed based on three-dimensional excitation–emission matrix fluorescence spectroscopy and LC-MS. More importantly, the toxicity changes during the degradation of tetracycline were evaluated using a bioluminescence inhibition test and the Ecological Structure Activity Relationship (ECOSAR) program. The toxicity of most of the intermediates was obviously lower than that of tetracycline, which suggests the potential of Fe@MoS2 in reducing the toxicity of effluents. This work provides a deeper understanding of the role of loaded Fe in piezo-catalysis and gives a new perspective for practical piezo-catalytic degradation to effectively reduce the amount and toxicity of antibiotics in water.